Comparison of Back Propagation Neural Network and Genetic Algorithm Neural Network for Stream Flow Prediction. (28th August 2014) - Gowda, C. Chandre; Mayya, S. G.
Abstract : Comparison of stream flow prediction models has been presented. Stream flow prediction model was developed using typical back propagation neural network (BPNN) and genetic algorithm coupled with neural network (GANN). The study uses daily data from Nethravathi River basin (Karnataka, India). The study demonstrates the prediction ability of GANN. The statistical tests show that GANN model performs much better when compared to BPNN model.